Pengembangan IMTAK sebagai Upaya Membangun Ukhuwah Islamiyah: Studi Kasus PAI Berwawasan Multikultural - Toba, Rostanti; Bukhari, Ahmad (FENOMENA, 2015)
The objective of this study was to find out the implementation of multiculturalism of the Islamic values and how to develop the multiculturalism of the Islamic values at SMA 5 Samarinda. The result of data findings shows that the implementation of multiculturalism of the Islamic values at SMA 5 Samarinda covers some following sectors, they are: 1) the implementation of asmaâ€™ul husna values, 2) love other moslems, 3) strong attitude, 4) never give up, 5) religious values action, 6) appreciating others, 7) caring, 8) sharing to others, 9) democratic, 10) khalifah concept, and 11) tolerance to other religion. In terms of how to develop of the multiculturalism of the Islamic values at SMA 5 Samarinda, it was found that the result of mean score of the questionnaire was 2.86 or it is categorized â€œVery Goodâ€. To sum up, the development of the multiculturalism of the Islamic values at SMA 5 Samarinda can be categorized as a Very Good.